CORPORATE SOCIAL RESPONSIBILITY, POLITICAL CONNECTIONS, AND TAX AVOIDANCE: (EMPIRICAL EVIDENCE FROM ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - Adinda Suci Cahya Ningtyas; Ni Nyoman Alit Triani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study examines whether Corporate Social Responsibility (CSR) is related to Tax Avoidance and whether Political Connection modifies that relationship. Energy-sector companies are selected as the empirical setting because they operate at a large scale, have complex business activities, and depend heavily on natural resources. These characteristics place substantial social and environmental responsibilities on the firms and make the sector relevant to the research question.Methods: A quantitative design is applied to secondary data drawn from the 2019-2022 annual reports of energy-sector companies listed on the Indonesia Stock Exchange (IDX). The observations cover multiple firms and multiple years, producing panel data that combine cross-sectional and time-series dimensions. Purposive sampling is used within a non-probability sampling approach to determine the sample. SPSS is employed for descriptive analysis, classical assumption testing, and hypothesis testing with Moderated Regression Analysis (MRA).Results: Statistical testing finds no significant relationship between Corporate Social Responsibility and Tax Avoidance. The interaction between CSR and Political Connection is also insignificant. Political Connection, therefore, does not produce a detectable change in the CSR-Tax Avoidance relationship among the energy-sector companies examined. Overall, CSR, Political Connection, and the interaction term provide a limited explanation of Tax Avoidance among energy-sector issuers listed on the Indonesia Stock Exchange.Conclusion and Suggestion: Subsequent studies should add other financial and governance determinants to the model so that corporate tax-avoidance behavior can be explained more comprehensively. Keywords: Corporate Social Responsibility, Political Connections, Tax Avoidance